Study on the dispersion of radon (222Rn) in geological objects in Bat Xat district, Lao Cai province, Northern Vietnam - Van Dung Nguyen; Thi Lan Anh Vu; Thi Ha Thu Dang; Ha Phuong Vu; Thi Cuc Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
The Bat Xat district in the Lao Cai province of Vietnam has enormous potential for resources of copper and rare earth minerals. In fact, exploration and exploitation activities for these minerals have brought about positive economic benefits to this area in recent years. However, this activity also brings about negative impacts on the environment and the surrounding population. The mineral deposits in this area contain a significant content of radioactive substances like uranium and thorium that radiate radon (222Rn) and thoron (220Rn). Therefore, the aim of this study is to investigate the distribution of radon as a function of depth of geological objects in the study areas. Results of this study showed that radon concentration has an exponential distribution with soil depth with R2 ranging from 0.87 to 0.97. It was found that radon concentration in sand was higher than that in clay and soils mixed with gravels. It was also shown that the density and moisture content of the soil is inversely proportional to the diffusion length of radon in the soil.